Male victims of non-sexual and non-domestic violence: service needs and experiences in court - Hannah Andrevski
This report presents the findings of a study that explored the experiences and support needs of male victims of violence living in New South Wales. Abstract: While a great deal of research has been undertaken into female victims of violence, male-focused victimology research undertaken in Australia and internationally is scant. This means it is currently unclear what the support needs of male victims are and if these support needs are being met by the currently available services and programs. The findings of this report derive from a study commissioned by the NSW Department of Attorney General and Justice Victims Services that sought to address this knowledge gap by exploring the experiences and support needs of male victims of violence (excluding sexual assault and domestic violence) living in New South Wales. The study involved a comprehensive review of the currently available literature and interviews and focus groups with criminal justice and support service representatives who have contact with male victims of violence as part of their everyday work